Investigation the Variation of Bulk Modulus of Elasticity on The Performance of Conventional Electrohydraulic System (Journal of University of Babylon for Engineering Sciences, 2019)
Basically,  all hydraulic performance systems are extremely reliant on the  rising of the oil temperature, due to an increase in the pressure, decrease lubricate moving parts, increases leakage and dissipate heat. This could lead to the variation in bulk modulus of elasticity for different working cnditions, which  could be affected in the performance of the  system. Accordingly, an attempt was made to examine   the effect of the bulk modules of elasticity on the accurate position. Six pressure suppliers were  critically used (20, 30, 40, 50, 60 and 70) bar at  five oil temperatures (25, 40, 50, 60 and 70) °C. Experimental results showed that the maximum variation percentage in the actuator displacement at the  same load occurred at  70 °C  oil temperature and there were 4.252%, 7.25% , 9.154% , 9.253%, 8,727%, 15.476 and 19.23% in 20 , 30, 40, 50, 60 and 70 bar pressure supply,  respectively.